Autonomic modulations of heart rate variability are associated with sports injury incidence in sprint swimmers - Lima-Borges, Dayanne S.; Martinez, Paula F.; Vanderlei, Luiz Carlos M. [UNESP]; Barbosa, Fernando S. S.; Oliveira-Junior, Silvio A. (Taylor & Francis, 2018)
Objectives: Young athletes’ participation in competitive sports is becoming increasingly common, and this increased involvement raises concerns about the occurrence of overtraining and sports injuries. Since these issues are poorly understood, this study analyzed heart rate variability, stress/recovery relationship, and sports injury incidence during a training macrocycle of young sprint and endurance swimmers. Methods: Thirty teenage swimmers (aged 12 to 17 years) were divided into two groups as follows: Sprint (n = 17) and Endurance (n = 13). Subjects were evaluated over 20 weeks, based on the following three schedules: general, specific, and competitive. In addition to heart rate variability and sports injury incidence, the Recovery-Stress-Questionnaire of Athletes was used to analyse stress/recovery states in athletes. All procedures were developed at the initial moment and at the end of each periodization step. Results: The Sprint group presented a reduced standard deviation of normal-normal beats (73.0 ± 6.6 vs. 54.1 ± 3.5 ms; p < 0.05) and root mean square of the successive differences (55.3 ± 6.2 vs. 42.0 ± 3.7 ms; p < 0.01) from the period of general preparation until the time of competition. Recovery-stress monitoring was affected only by the swimming training periodization (p < 0.05). During the general period, differences between recovery and stress scales were correlated directly with the root mean square of the successive differences (r = 0.576; p = 0.001), the standard deviation of instantaneous variability beat-to-beat (r = 0.521; p = 0.003) and the triangular index (r = 0.476; p = 0.008). Differences between general recovery and stress scales were inversely correlated with geometric indexes after the specific training period. Moreover, the Sprint group showed a higher incidence of sports injury than the Endurance group (0.0214 ± 0.0068 vs. 0.0136 ± 0.0050 cases/1000 hours). Conclusion: Sprint training was associated with progressive activation of the sympathetic nervous system as well as a higher incidence of sports injury in comparison to endurance swimming during a training macrocycle.
Keywords: athletic injuries; athletic performance; autonomic nervous system; exercise; Fatigue